Does Winter Wheat Yield Response to Fungicide Application Depend on Nitrogen Management? - J. A. Romero Soler; L. O. Pradella; N. Giordano; G. Cruppe; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
Nitrogen and fungicide are among the more important management tools to increase wheat (Triticum aestivumL.) grain yield in Kansas. However, there is limited information on whether hard red winter wheat grain yield is impacted by the interaction of nitrogen rates and foliar fungicide application. Thus, our objective was to evaluate the effects of different N rates with or without a fungicide application at Feekes 10.5 on grain yield of two winter wheat genotypes with contrasting disease resistances to leaf and stripe rust. Eleven field experiments were established across Kansas using a factorial structure of two fungicide management options (either no fungicide or 13 fl oz of Nexicor per acre), five N rates (0, 30, 60, 90, and 120 pounds of N per acre), and two genotypes (Larry and Zenda) in a split-split plot design during the 2021–2022 growing season. There was a significant interaction between genotype and environment where Larry out-yielded Zenda in anywhere from 3.1 to 15 bu/a. There was a significant interaction between N rate and environment, likely due to the initial soil NO3-N and yield potential, as grain yield ranged from less than 34 to more than 81 bu/a. Increases in fractions of canopy cover in response to N fertilization and fungicide application explained about 29% and 15% of the increases in grain yield, respectively. There was a slightly greater crop yield response to foliar fungicide application as the N supply increased, from a nearly null difference at low N supply to as much as 5.9% for total N supply greater than 160.7 lb of N/a. In dry conditions with minimal disease incidence, winter wheat response to N availability differed in each environment, but there was only a marginal response to foliar fungicide.
Keywords: wheat; fungicide; varieties; nitrogen